2016
DOI: 10.11648/j.js.20160405.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transurethral Enucleation Resection of the Prostate for Benign Prostatic Hyperplasia on Immune and Stress Response

Abstract: This thesis aims to examine the effects of the systemic immune response triggered by the transurethral enucleation and resection of the prostate (TRERP). 60 patients with benign prostatic hyperplasia (BPH) were randomly classified into enucleation group and resection group. The level of WBC, serum IL-6, IL-8, CRP, IgG, IgA, IgM, CD4+, CD8+,and ratio of CD4+ to CD8+ (BPH)were compared and analyzed preoperatively and on the 1st, 3rd, 5th of postoperative day. The result demonstrates the statistical significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
2
0
0
Order By: Relevance
“…Plasma IL-8 concentrations showed a significant increase post-TTPB, and this supports the report by Yuan [ 36 ], who also observed an increase in IL-8 an hour post-TURP. The significant increase in plasma IL-8 concentrations observed in this study is consistent with reports that an acute-phase immune response occurs within 2 h of stimuli challenge [ 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Plasma IL-8 concentrations showed a significant increase post-TTPB, and this supports the report by Yuan [ 36 ], who also observed an increase in IL-8 an hour post-TURP. The significant increase in plasma IL-8 concentrations observed in this study is consistent with reports that an acute-phase immune response occurs within 2 h of stimuli challenge [ 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…The present study found a significant increase in plasma IL-6 concentrations at 120 min and 240 min post-TTPB, which follows a similar pattern of change as reported after transurethral resection of the prostate (TURP) [36] and shock wave lithotripsy for kidney stones [37], suggesting an immune and stress (inflammatory) response to the procedure.…”
Section: Discussionsupporting
confidence: 86%